Needs Analysis for Developing of Bahasa Indonesia’s Placement Test at SPK School in Tangerang - Yoanita Muliawan (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This preliminary study aims to confirm the need to develop a bahasa Indonesia placement test for an International Baccalaureate (IB)-based SPK school in Tangerang. The researcher uses the needs analysis method by collecting quantitative and qualitative fata from the entire audiences through interviews, surveys, documentation and field observations. From this study it was concluded that the development of a better Indonesian placement test is needed in terms of test questions, contents and thoroughness of the rubric, and procedures in marking. It is the researcher’s expectation that the results of this study will be of benefit to other IB-based schools in need for a more accurate Indonesian placement test. Keywords: placement test, Indonesian language, IB Abstrak Penelitian ini adalah penelitian pendahuluan yang bertujuan untuk mengonfirmasi kebutuhan pengembangan tes penempatan bahasa Indonesia yang dipakai di sebuah sekolah SPK berbasis International Baccalaureate (IB) di Tangerang. Peneliti memakai metodeanalisakebutuhandengancaramengumpulkan data kuantitatif dan kualitatif dari seluruh audiens melalui wawancara, survei, dokumentasi, dan observasi lapangan. Dari penelitian ini, disimpulkan perlunya pengembangan tes penempatan bahasa Indonesia yang lebih baik dalam hal materi soal, isi dan kelengkapan rubrik, serta prosedur dalam melakukan penilaian. Hasil dari penelitian ini diharapkan dapat membantu sekolah-sekolah berbasis IB yang juga membutuhkan tes penempatan bahasa Indonesia yang lebih akurat. Kata kunci: tes penempatan, bahasa Indonesia, IB